Carbon dioxide (C02) Adsorption Experiment on Indonesia Coal Seam, A Case Study from South Sumatra Basin - , Ferian Anggara ([Yogyakarta] : Departments of Geological Engineering,Facultyof En, 2009)
C02 adsorption experiments up 5.7 MPa at 313 OK (Tc : 304.1 K